Selective Ablation of the Androgen Receptor in Mouse Sertoli Cells Affects Sertoli Cell Maturation, Barrier Formation and Cytoskeletal Development - Willems, Ariane; Batlouni, Sergio R. [UNESP]; Esnal, Arantza; Swinnen, Johannes V.; Saunders, Philippa T. K.; Sharpe, Richard M.; Franca, Luiz R.; De Gendt, Karel; Verhoeven, Guido (Public Library Science, 2010)
The observation that mice with a selective ablation of the androgen receptor (AR) in Sertoli cells (SC) (SCARKO mice) display a complete block in meiosis supports the contention that SC play a pivotal role in the control of germ cell development by androgens. To delineate the physiological and molecular mechanism responsible for this control, we compared tubular development in pubertal SCARKO mice and littermate controls. Particular attention was paid to differences in SC maturation, SC barrier formation and cytoskeletal organization and to the molecular mediators potentially involved. Functional analysis of SC barrier development by hypertonic perfusion and lanthanum permeation techniques and immunohistochemical analysis of junction formation showed that SCARKO mice still attempt to produce a barrier separating basal and adluminal compartment but that barrier formation is delayed and defective. Defective barrier formation was accompanied by disturbances in SC nuclear maturation (immature shape, absence of prominent, tripartite nucleoli) and SC polarization (aberrant positioning of SC nuclei and cytoskeletal elements such as vimentin). Quantitative RT-PCR was used to study the transcript levels of genes potentially related to the described phenomena between day 8 and 35. Differences in the expression of SC genes known to play a role in junction formation could be shown from day 8 for Cldn11, from day 15 for Cldn3 and Espn, from day 20 for Cdh2 and Jam3 and from day 35 for ZO-1. Marked differences were also noted in the transcript levels of several genes that are also related to cell adhesion and cytoskeletal dynamics but that have not yet been studied in SC (Actn3, Ank3, Anxa9, Scin, Emb, Mpzl2). It is concluded that absence of a functional AR in SC impedes the remodeling of testicular tubules expected at the onset of spermatogenesis and interferes with the creation of the specific environment needed for germ cell development.